Assessing the Validity of the Trauma Inventory for Partners of Sex Addicts (TIPSA). Issue 1 (2nd April 2020) - Vogeler, Heidi A.; Fischer, Lane; Bingham, Jennie L.; Hansen, Kristina S. W.; Heath, Melissa A.; Jackson, Aaron P.; Skinner, Kevin B.
Abstract: The purpose of this study was to both provide additional evidence of the psychometric properties of the Trauma Inventory for Partners of Sex Addicts (TIPSA), and add empirical evidence for the application of betrayal trauma theory outside the context of complex and/or historical trauma. It was hypothesized that reliability coefficients for TIPSA would exceed 0.70; TIPSA and PTSD Checklist for DSM 5 (PCL-5) scores would be significantly positively correlated; TIPSA and Composite Codependency Scale (CCS) scores would not be significantly correlated; and neither Adverse Childhood Experiences (ACE) nor Benevolent Childhood Experiences (BCE) scores would be significantly correlated with, or have a significant effect on, TIPSA or PCL-5 scores. All reliability estimates were above 0.70, and correlation between TIPSA and PCL-5 produced a Pearson's r of 0.851 (p = 5.541 E-55), which indicated a large effect size. Correlations with additional measures produced statistically significant, yet small to weak, effect sizes (CCS: r = 0.292; ACE: r = −0.173; BCE: r = 0.244). This evidence established convergent validity of TIPSA as a measure of trauma symptoms, divergent validity of TIPSA as a measure of codependency, and added empirical evidence for utilizing betrayal trauma theory in this context.